Pemanfaatan Media Digital dalam Meningkatkan Efektivitas Pembelajaran PAI untuk Siswa SMA Islam Plus Adzkia Medan - Muhammad Yazid Maulana; Isman Efendi Limbong (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of digital technology has brought significant changes in the field of education, particularly in Indonesia, including in the teaching of Islamic Religious Education (PAI). Teachers are required to adapt by utilizing digital media so that the learning process becomes more effective, engaging, and aligned with the needs and characteristics of Generation Z students. This study aims to present the use of digital media in improving the effectiveness of PAI learning for students at SMA Islam Plus Adzkia Medan. The research method employed is descriptive qualitative, using data collection techniques such as observation, interviews, and documentation. The findings of this study indicate that the use of digital media, such as interactive presentations for students, visually appealing learning videos, and digital platforms, can enhance student motivation, participation, and comprehension of PAI material delivered by teachers. Digital media also helps teachers deliver content in a more structured, clear, and accessible manner for students. However, despite its advantages, digital media is not without challenges, such as limited internet access and a lack of digital skills among some students. Overall, the use of digital media provides a positive impact on the effectiveness of PAI learning at SMA Islam Plus Adzkia Medan and therefore needs to be optimized through teacher training, improvement of school facilities, and strengthening students’ digital literacy.